Using the Theories of Planned Behaviour and Leisure Constraints to study Fitness Club Members' behaviour after Covid-19 Lockdown. Issue 2 (4th March 2022) - Alexandris, K.; Karagiorgos, T.; Ntovoli, A.; Zourladani, S.
ABSTRACT: This paper aimed to examine fitness club members' willingness to start exercising in the clubs with the end of the lockdown. The Theory of Planned Behaviour (TPB) was used in order to explore which of its components can predict club members' intention; furthermore, the degree to which leisure constraints can predict the formation of the elements of the TPB was tested. Three hundred and twenty three (N = 323) questionnaires were used; they were collected with an on-line survey, during the second lockdown in Greece. The results indicated that almost one out of three of the club members do not intend to return to the clubs when they are allowed to open. All the three elements of the TPB were contributed to the prediction of Intentions, with the Attitudes having the highest contribution. The Covid19, Hygienic and Financial constraint dimensions were the most influential on the formation of the elements of the TPB. The theoretical and applied implications of these results are discussed.